Prevalence and incidence of systemic sclerosis in southern Sweden: population-based data with case ascertainment using the 1980 ARA criteria and the proposed ACR-EULAR classification criteria. Issue 10 (29th July 2013) - Andréasson, K; Saxne, T; Bergknut, C; Hesselstrand, R; Englund, M
Abstract : Objectives: To estimate the prevalence and incidence of systemic sclerosis (SSc) in southern Sweden. Methods: In Skåne, the southernmost region of Sweden (total population 1.2 million), healthcare provided is registered in the Skåne Healthcare Register. We identified all Skåne residents who had received an International Classification of Diseases 10 diagnosis of SSc (M34) or Raynaud's phenomenon (I73.0) between 1998 and 2010. Every single case was ascertained by review of medical records in reference to the 1980 American Rheumatism Association preliminary classification criteria for SSc and the proposed American College of Rheumatology (ACR)-European League Against Rheumatism (EULAR) classification criteria presented at the ACR/Association of Rheumatology Health Professionals Annual Meeting 2012. We calculated the point prevalence by the end of 2010 by linkage with the population register to exclude deceased persons and we also estimated the mean annual cumulative incidence for 2006–2010. Results: Using the 1980 ARA criteria, the adult prevalence and annual incidence of SSc in the Skåne region were 235 and 14 per 1 million inhabitants respectively. Applying the proposed ACR-EULAR criteria, the corresponding figures were 305 and 19 per 1 million inhabitants. A majority (82%) of the prevalent cases had the limited cutaneous SSc subtype. Conclusions: The prevalence and incidence of SSc in southern Sweden, based on the 1980 ARA criteria, are higher than previously reported in northern Europe and do not support the concept of a north-south gradient of SSc occurrence in Europe. Application of the proposed ACR-EULAR classification criteria in this population results in about 30–40% higher estimates of SSc prevalence and incidence compared to the 1980 ARA criteria.